Akurasi Diagnosis Pemeriksaan Biopsi Aspirasi Jarum Halus Tumor Tulang di Departemen Patologi Anatomik FKUI/RSCM Tahun 2015- 2019 - Putri, Vabiayu; Stephanie, Marini (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundFine needle aspiration biopsy (FNAB) is a safe and rapid technique and has an important role in making the preoperative diagnosisof bone tumors because it can help clinicians determine treatment for patients. This retrospective study aims to assess the accuracyof the FNAB cytological examination compared with the histopathological examination in preoperative diagnosis of bone tumors.MethodsThe data comes from the archives of the Department of Anatomic Pathology, FKUI/RSCM 2015-2019 in the form of a cytologicalexamination of FNAB lesions on bone. Then the histopathological examination data were searched for each cytology preparation.There were 133 pairs of cytology, and histopathology preparations. The preparations were reviewed by the investigator andsupervisor, assessed for the suitability of the cytologic diagnosis, and compared with the histopathological diagnosis.ResultsThere were 84 (63.2%) cases of malignant tumors, 44 (33.1%) cases of benign tumors, and 5 (3.7%) cases of non-tumors. Thediagnostic test results showed an accuracy rate of 86.5% with a sensitivity of 85.9%, a specificity of 100%, a positive predictivevalue (PPV) of 100%, and a negative predictive value (NPV) of 21.7%.ConclusionFNAB cytology examination of bone tumors that have adequate sample quality, supported by complete clinical information andinformative radiological images can produce an accurate preoperative diagnosis